Comprehensive Study of Licensing Policy and Benefits of Danantara in The Perspective of Human Rights and Maqashid Syari'ah - Muhammad Salman Alfansuri Jacob; R.Asep Hamdan Munawar; Muflih Adi Laksono; Yusuf; Nilfatri (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is qualitative research with a descriptive approach, namely an approach that aims to comprehensively describe DANATARA, Human Rights, and Maqashid Sharia one by one. The data used in this study is secondary data that the researcher obtained indirectly from scientific articles in scientific magazines and credible websites. The conclusion in this article show that the existence of Danatara is in line with the principles contained in human rights and maqashid syari'ah because it aims to manage state assets optimally which can ultimately prosper the people and create problems. The welfare of the people is an achievement of a country as well as a concrete form of protecting the right to life of the people. From the perspective of maqashid syari'ah, the welfare of the people is also one of the maslahah referred to by syahtibi and loved by Allah SWT.